Combining ability of yield and its components in some sesame (Sesamum indicum L.) cultivars and lines - Ali, Khalafalla; El Ahmadi, Abdalla (المجلة الزراعية; مجلد 9 عدد 1 (2011), 2011)
Eight sesame lines were selected as parents from the sesame breeding program, Gedarif Research Station of the Agricultural Research Corporation (ARC), Sudan. The parents were crossed in all possible diallel combinations (without reciprocals) to produce 28 single-cross hybrids. The parents and 28 F 1 generatins were evaluated under rains for two consecutive seasons (2005 and 2006) at Gedarif Research Station. Four of the parents were released varieties viz : Ziraa-9, Kenana-2, Promo and Gedarif-1, and the other four were advanced lines. The experiment was arranged in a randomized complete block design with three replicates to elucidate general and specific combining ability for yield and yield components among 36 sesame genotypes. Data were recorded on days to 50% flowering; days to maturity; plant height; number of branches/plant; number of capsules/plant;  height to first capsule; height to first branch; capsule length; 1000 seeds weight; seed yield/plant and seed yield/ha. Analysis of combining ability revealed the importance of both additive and non-additive gene action for inheritance of the measured traits. The magnitudes of general combining ability (GCA) variances were greater than the respective variances due to specific combining ability (SCA). Additive gene action was predominant for days to 50% flowering, days to maturity, plant height, height to first capsule, capsule length and 1000-seed weight. Non-additive gene action predominated seed yield/plant and seed yield/ha. The GCA effects revealed that Gd2002SPSN29, Ziraa-9 and Gedarif-1 were the best combiners, since they recorded significant GCA effects in either direction for most of the measured traits. The parent Gd2002SPSN53 was the poorest combiner of all the parents used in this study. Considerable number of crosses showed significant SCA effects. The cross combinations Gd2002SPSN.53 x Gedarif-1, Gd2002SPSN.53 x Promo and Gd2002SPSN.14 x Ziraa-9 exhibited significant positive SCA effects for seed yield/ha, with a reasonable yields of 1081, 841 and 810 kg/ha, respectively. The study suggested that further testing would be needed to confirm consistency of these crosses in term of their seed yield and stability.      تم اختبار ثمانية اباء من برنامج تربية السمسم، محطة بحوث القضارف، السودان. هجنت الاباء الثمانية من جهة واحدة مع بعضها للحصول على 28 هجين. تم تقويم ثمانية طرازاً  وثمانية وعشرين هجيناً فى موسمين مطريين متتاليين 2005 و 2006 بمحطة بحوث القضارف. الأصناف زراعة-9، كنانة-2، برومو وقضارف-1 مجازة. أما الأربعة أباء الاخرين تمثل طرز متقدمة. نفذت التجربة باستخدام القطاعات العشوائية الكاملة بثلاث مكررات لمعرفة القدرة التوافقية العامة والخاصة للانتاجية ومكوناتها بين 36 سلالة من السمسم.  قيست البيانات التالية: عدد الأيام حتى 50% ازهار، عدد الأيام حتى النضج، طول النبات، عدد الفروع فى النبات، عدد الكبسولات فى النبات، ارتفاع أول فرع، ارتفاع أول كبسولة، طول الكبسولة، وزن ال 1000 بذرة، الانتاجية للنبات والانتاجية للهكتار. أظهر تحليل القدرة التوافقية اهمية كل من الفعل الجينى الاضافى والفعل الجينى غير الاضافى فى توريث الصفات المقاسة. كان التباين فى القدرة التوافقية العامة اكبر من التباين فى  القدرة التوافقية الخاصة والفعل الجينى الاضافى سائدا فى صفات عدد الايام حتى 50% ازهار، عدد الايام حتى النضج، طول النبات، ارتفاع اول كبسولة، طول الكبسولة ووزن 1000 بذرة. اما الفعل الجينى غير الاضافى فقد كان سائدا فى صفة الانتاجية للنبات والانتاجية للهكتار. أظهر أثر القدرة التوافقية العامة ان الأباء Gd2002SPSN29, Ziraa-9 وGedarif-1 هم الافضل للقدرة التوافقية العامة، حيث انها سجلت اثرا معنويا للقدرة التوافقية العامة فى اى من الاتجاهين لمعظم الصفات المقاسة. الاب Gd2002SPSN53 هو الاضعف للقدرة التوافقية العامة. أظهرعدد مقدر من الهجن اثرا معنويا فى القدرة التوافقية الخاصة. فالهجن Gd2002SPSN.53 x Gedarif-1, Gd2002SPSN.53 x Promo and Gd2002SPSN.14 x Ziraa-9  اظهرت اثرا معنويا موجبا فى القدرة التوافقية الخاصة لصفة الانتاجية للهكتار، بانتاجية مناسبة قدرها 1081، 841 و810 كجم/هكتار على التوالى. تقترح الدراسة الحوجة لمزيد من الاختبارات لتأكيد ثبات انتاجية هذه الهجن فى المواسم والمواقع المختلفة.